Improving the ability of subtraction through numerical card puzzles media for students with hearing impairment - Fatmawati Fatmawati; Safaruddin Safaruddin (Journal of Counseling and Educational Technology, 2018)
There are so many components that should be prepared well in teaching and learning process, one of them is media. Media has a function to attract the students' attention and help them understand the material easier. However, many teachers cannot used the media properly, especially for students with hearing impairment who had problem in doing subtraction. This was an experimental research with pre-experimental design or quasi experiment. The purpose of this research was to reveal the effect of using numerical card puzzles and know the differences between two different variables. The design was one group pre-test posttest which control class was also experimental class. The research was conducted at class V with five students who have hearing impairment. The sample was chosen by using a total sampling method. The data was analyzed by using Mann Whitney with 95% and α= 0.005.The research result shows that: first, the students learning results were low when the teacher use blackboard as media. Second, student’s learning results improved significantly when the teacher used numerical card puzzles. The test showed that Ucount= 25 and Utable = 8. Based on the test, the hypothesis is accepted with Ucount ≥ Utable can be concluded that numerical card puzzles is effective to improve student with hearing impairment.